Network intrusion intention analysis model based on Bayesian attack graph - Zhiyong LUO; Xu YANG; Jiahui LIU; Rui XU (Tongxin xuebao)
Aiming at the problem of ignoring the impact of attack cost and intrusion intention on network security in the current network risk assessment model,in order to accurately assess the target network risk,a method of network intrusion intention analysis based on Bayesian attack graph was proposed.Based on the atomic attack probability calculated by vulnerability value,attack cost and attack benefit,the static risk assessment model was established in combination with the quantitative attack graph of Bayesian belief network,and the dynamic update model of intrusion intention was used to realize the dynamic assessment of network risk,which provided the basis for the dynamic defense measures of attack surface.Experiments show that the model is not only effective in evaluating the overall security of the network,but also feasible in predicting attack paths.